Campylobacter jejuni capsular genotypes are related to Guillain–Barré syndrome. (September 2015) - Heikema, A.P.; Islam, Z.; Horst-Kreft, D.; Huizinga, R.; Jacobs, B.C.; Wagenaar, J.A.; Poly, F.; Guerry, P.; van Belkum, A.; Parker, C.T.; Endtz, H.P.
Abstract: In about one in a thousand cases, a Campylobacter jejuni infection results in the severe polyneuropathy Guillain–Barré syndrome (GBS). It is established that sialylated lipo-oligosaccharides (LOS) of C. jejuni are a crucial virulence factor in GBS development. Frequent detection of C. jejuni with sialylated LOS in stools derived from patients with uncomplicated enteritis implies that additional bacterial factors should be involved. To assess whether the polysaccharide capsule is a marker for GBS, the capsular genotypes of two geographically distinct GBS-associated C. jejuni strain collections and an uncomplicated enteritis control collection were determined. Capsular genotyping of C. jejuni strains from the Netherlands revealed that three capsular genotypes, HS1/44c, HS2 and HS4c, were dominant in GBS-associated strains and capsular types HS1/44c and HS4c were significantly associated with GBS (p 0.05 and p 0.01, respectively) when compared with uncomplicated enteritis. In a GBS-associated strain collection from Bangladesh, capsular types HS23/36c, HS19 and HS41 were most prevalent and the capsular types HS19 and HS41 were associated with GBS (p 0.008 and p 0.02, respectively). Next, specific combinations of the LOS class and capsular genotypes were identified that were related to the occurrence of GBS. Multilocus sequence typing revealed restricted genetic diversity for strain populations with the capsular types HS2, HS19 and HS41. We conclude that capsular types HS1/44c, HS2, HS4c, HS19, HS23/36c and HS41 are markers for GBS. Besides a crucial role for sialylated LOS of C. jejuni in GBS pathogenesis, the identified capsules may contribute to GBS susceptibility.